2018
DOI: 10.3892/etm.2018.6412
|View full text |Cite
|
Sign up to set email alerts
|

Clinical therapy of hyaluronic acid combined with platelet‑rich plasma for the treatment of knee osteoarthritis

Abstract: Knee osteoarthritis is the most common degenerative disease of the joints caused by articular cartilage injury, degradation of the joint edge and subchondral bone hyperplasia. Various treatments are used to alleviate the symptoms of patients with knee osteoarthritis, including analgesics and intra-articular injections. Platelet-rich plasma (PRP) is an autologous and multifunctional platelet concentrate of the blood, which stimulates the cartilage healing process and improves the damage caused by articular dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(112 citation statements)
references
References 40 publications
3
105
1
3
Order By: Relevance
“…This metaanalysis found that PRP combined with HA at 6 months after treatment was superior to PRP alone, which may suggest that PRP combined with HA may be a better treatment for patients with long-term knee pain in the future. Previous studies have shown that PRP combined with HA for KOA can reduce WOMAC pain scores more than PRP alone can, which is consistent with the present findings [18]. In terms of the improved WOMAC Function Score and WOMAC Total Score, intra-articular injection of PRP combined with HA, compared with PRP alone, can improve patients' knee joint function scores and overall WOMAC scores.…”
Section: Discussionsupporting
confidence: 92%
“…This metaanalysis found that PRP combined with HA at 6 months after treatment was superior to PRP alone, which may suggest that PRP combined with HA may be a better treatment for patients with long-term knee pain in the future. Previous studies have shown that PRP combined with HA for KOA can reduce WOMAC pain scores more than PRP alone can, which is consistent with the present findings [18]. In terms of the improved WOMAC Function Score and WOMAC Total Score, intra-articular injection of PRP combined with HA, compared with PRP alone, can improve patients' knee joint function scores and overall WOMAC scores.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the synergy between combined PRP and HA treatment was further investigated and compared with each of them alone and with a placebo, via intra-articular injections in a total of 360 patients with knee osteoarthritis [145], demonstrating significantly reduced pain and decreased immune response, as well as PRP treatment compared with low and high molecular weight HA [143].…”
Section: Knee Osteoarthritismentioning
confidence: 99%
“…These growth factors have a direct effect on the physical and biomechanical properties of the joint, cartilage biosynthesis and degradation. In addition, they possess anti-in ammatory effects and a direct analgesic effect related to interaction with pain receptors [42].…”
Section: Growth Factors -The Healing Promotersmentioning
confidence: 99%